Stage-specific sex differences in Drosophila immunity to parasites and pathogens - Kraaijeveld, A; Barker, C; Godfray, C (2008)
Arguments from life-history theory predict that other things being equal females are likely to invest more in defence against parasites and pathogens than males. This is either because males and females differ in behaviour or, more importantly, because the variance in mating success is typically higher in males than in females. Such effects are likely to be most pronounced in those developmental stages where sex differences are greatest. In most organisms, but especially in holometabolous insects, this will be the adult stage. We explored sex-specific resistance to four natural enemies of Drosophila melanogaster that attack the insect at different developmental stages: the larval parasitoid Asobara tabida, the pupal parasitoid Pachycrepoideus vindemiae; and the adult pathogens Beauvaria bassiana (a fungus) and Tubulinosema kingi (a microsporidian). Measures of resistance were designed to reflect the four species' natural history. Female larvae were able to defend themselves more strongly against A. tabida than males and there was weak evidence that adult females suffered less from microsporidian attack than males. No differences were found for the other two species. Our results provide some support for lower investment in defences in males, and we discuss why the strongest effect was found at the larval rather than the adult stage contrary to our prediction. © 2007 Springer Science+Business Media, Inc.